Autodesk revit architecture 2016 essentials - Duell, Ryan (Wiley, 2015)
This new edition includes expanded information on rendering and visualization, and a new discussion surrounding effective work sharing, details and annotations, drawing sets, and professional workflows. The companion website features additional tutorials, plus downloadable data sets that allow you to jump in at any point and compare your work to the pros.